Pengendalian Kelembaban dan PH pada Alat Semai Otomatis berdasarkan Sensor Kelembaban, PH, dan Arduino menggunakan Regresi Linier - Dody Kristian Manalu; Hurriyatul Fitriyah; Edita Rosana Widasari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Humidity and acidity (PH) are essential factors because if rockwool is too acidic not moist or dry the plant growth rate will be slower. A pH that is too acidic or alkaline can result in the deposition of nutrients and inorganic substances in hydroponics so that plant growth is less than optimal. Temperature also plays an important role in plant growth. With this the author will create a system using a Soil Moisture sensor a PH-4502C sensor and a Linear Regression method that is connected to the Arduino Uno and will issue an output that is flowing water through a water pump with the condition that the humidity in the rockwool has not met the set point as well as for the pH will flow PHUP water if the pH conditions on Pakcoy plants are low and will flow PHDOWN if the pH conditions on Pakcoy plants are high. For this system there are 25 training data including 20 data as training data and 5 data as test data. The results obtained from the Linear Regression test are MAPE and RMSE for humidity 5,1% and 0.12 while for PH are 5,2% and 0.17 and the results of Pakcoy seed plants can grow perfectly as expected.